Analisis Peran Modalitas Bourdieu dalam Membentuk Identitas Merek (Brand Identity) Sekolah - Mohammad Mansur; Amrulloh; Dhukrul Hakim (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2026)
School brand identity has become a strategic issue in the management of educational institutions, particularly amid the increasing competition among Islamic educational institutions. A strong identity not only functions as an external image but also serves as a reflection of the school’s values, culture, and social capital. Therefore, this study aims to identify and analyze the role of various forms of capital in Pierre Bourdieu’s theory of capital—namely social, cultural, economic, and symbolic capital—in shaping the brand identity of Islamic educational institutions. This research employs a qualitative method with a case study approach at MI Plus Darul Falah. Data collection techniques include observation, in-depth interviews, and documentation. Data were analyzed using the interactive model developed by Miles and Huberman. The findings reveal that all four forms of capital significantly contribute to the formation of the institutional brand identity of the madrasah. Social capital is built through networks of relationships with the community, parents, and alumni. Cultural capital develops through strong scholarly traditions and religious practices. Economic capital is supported by parental participation and effective school resource management. Symbolic capital is manifested in the institution’s reputation and social status as a leading modern Islamic school. Altogether, these forms of capital shape a collective habitus that constructs the madrasah’s brand identity as a “madrasah of Qur’anic-mannered and high-achieving students.” This study also extends the field of school branding by demonstrating that school brand identity can be constructed through social practices, drawing on Pierre Bourdieu’s theory of capital and habitus.